Programa “reciuso” para desarrollar la capacidad genera acciones para conservar el ambiente en una Institución Educativa Primaria, Trujillo – 2019 - Cruz Gonzales, Margarita Amabela (2021)
The objective of the present work, it was to determine the influence of the “Reciuso” _x000D_ program in the improvement of the capacity generated actions to conserve the _x000D_ environment in the fourth – degree students of primary school of the experimental _x000D_ educational center “Rafael Narváez Cadenillas”, Trujillo-2019 .For which used him 48 _x000D_ students ' sample , 24 of the control group and 24 of the experimental group, to whom _x000D_ a Likert scale was applied to measure the level of capacity generated actions to _x000D_ conserve the environment, this instrument was formed for 20 items. Then the _x000D_ application of the program to the experimental group showed a significant _x000D_ improvement in the capacity to generate actions to conserve the environment, as _x000D_ evidenced by the test value t (9.596), which was greater than the significance t; _x000D_ Therefore, it is concluded that the program significantly improved capacity generates _x000D_ actions to conserve the environment.